FORMULASI DAN UJI AKTIVITAS GEL ANTIJERAWAT EKSTRAK UMBI BAKUNG (CRINUM ASIATICUM L.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS SECARA IN VITRO - Kumesan, Yuni Arista N; Yamlean,, Paulina V. Y.; Supriati, Hamidah S (UNIVERSITAS SAM RATULANGI, 2013)
Crinum asiaticum L. is a plant that has antibacterial activity toward Staphylococcusaureusbacteria, which is one of the pathogen bacteria that causing the acnes. This researchpurposed for made extract bulbs of Crinum asiaticum L. formula gel and tasted the physicalcharacteristic toward Staphylococcus aureus. The formulation of extract bulbs of Crinumasiaticum L. is made with variety of extract concentration, which 1%, 5%, and 10% withCMC-Na as the basic. Negative control used basis gel and positive control used ErymedÂ® gel(Erytromicin 2%). Gel that is produced by physically tested covers: organoleptis,homogeneity, pH, dispersive power, and consistency. Antibacterial activity tested is done bydiffusion method. Antibacterial activities data that are obtained by one way ANOVA withstandard trust is 95%. The result of this research showed that extract bulbs of Crinumasiaticum L. had antibacterial activities with average resistibility zone diameter for 1% (8,3mm) extract concentration, 5% (11,3 mm) extract concentration, 10% (16 mm) extractconcentration, positive control (32 mm), and negative control (0 mm). Positive controlcounted as vey strong resistibility, extract concentration 5% and 10% counted as strongresistibility, extract concentration 1% counted as fair resistibility and negative control notgiven antibacterial activities.Key words: extract bulbs of Crinum asiaticum L., CMC-Na, antibacterial, Staphylococcusaureus.